Karakteristik dan Kelimpahan Mikroplastik di Instalasi Pengolahan Air pada Perumdam Tirta Mayang Kota Jambi - Lionisa Agdiliani; Guntar Marolop Saragih; Siti Umi Kalsum (Universitas Batanghari Jambi, 2026)
The Batanghari River is the main raw water source for PERUMDAM Tirta Mayang, Jambi City. However, recent studies have revealed that the Batanghari River is contaminated with microplastics, ranging from 100–150 particles per liter at the intake area. This contamination has the potential to affect the quality of raw water entering the treatment plants. Microplastic contamination was evaluated at the Broni II Scada WTP owned by the Regional Water Company (PERUMDAM) Tirta Mayang in Jambi City, which has a processing capacity of 600 L/second. This 2023 study found 164 microplastic particles in water samples. These particles were predominantly fiber (2,420.1 particles/L) and filament (2,266.6 particles/L), with size variations between 0.00 and 4.00 mm, grouped into four classes, and five color variants (black, red, transparent, white, and yellow). The water treatment process showed fluctuating performance in removing microplastics. The highest decrease in abundance occurred in the sedimentation unit (58.33%), followed by the flocculator unit (29.41%), filtration (20%), the initial stage of raw water to intake (13.95%), and the coagulator unit (8.11%). In contrast, the reservoir unit did not record any removal efficiency. Based on the significance test, size dimension was the only characteristic that significantly influenced microplastic abundance (p < 0.05). Based on the risk index, the PRI value (78.3696 particles/L) placed the study site in the medium risk category, but the PLI value of 23.10 - 169.31 particles/L indicated that the microplastic pollution load in the area had entered the very high category.